International Transactions in Remittances : Guide for Compilers and Users (RCG). (Manuals and Guides, 2012)
This series contains practical "how-to" information for economists and includes topics such as tax policy, balance of payments statistics, external debt statistics, foreign exchange reserve management, and financial sector assessment.